Concurrent invasions of European starlings in Australia and North America reveal population‐specific differentiation in shared genomic regions - Natalie R. Hofmeister; Katarina C. Stuart; Wesley C. Warren; Scott J. Werner; Melissa Bateson; Gregory F. Ball; Katherine L. Buchanan; David W. Burt; Adam P. A. Cardilini; Phillip Cassey; Tim De Meyer; Julia George; et al. (Molecular Ecology, 2025)
A species' success during the invasion of new areas hinges on an interplay between the demographic processes common to invasions and the specific ecological context of the novel environment. Evolutionary genetic studies of invasive species can investigate how genetic bottlenecks and ecological conditions shape genetic variation in invasions, and our study pairs two invasive populations that are hypothesized to be from the same source population to compare how each population evolved during and after introduction. Invasive European starlings ( Sturnus vulgaris ) established populations in both Australia and North America in the 19th century. Here, we compare whole‐genome sequences among native and independently introduced European starling populations to determine how demographic processes interact with rapid evolution to generate similar genetic patterns in these recent and replicated invasions. Demographic models indicate that both invasive populations experienced genetic bottlenecks as expected based on invasion history, and we find that specific genomic regions have differentiated even on this short evolutionary timescale. Despite genetic bottlenecks, we suggest that genetic drift alone cannot explain differentiation in at least two of these regions. The demographic boom intrinsic to many invasions as well as potential inversions may have led to high population‐specific differentiation, although the patterns of genetic variation are also consistent with the hypothesis that this infamous and highly mobile invader adapted to novel selection (e.g., extrinsic factors). We use targeted sampling of replicated invasions to identify and evaluate support for multiple, interacting evolutionary mechanisms that lead to differentiation during the invasion process.

Feel-good songs: application of a novel playback paradigm to induce a positive affective state in juvenile male Wistar rats - Tayla J. Hammond; Sarah M. Brown; Simone L. Meddle; Birte L. Nielsen; Alistair B. Lawrence; Vincent Bombail (Applied Animal Behaviour Science, 2024)

Gene expression of sex steroid metabolizing enzymes and receptors in the skeletal muscle of migrant and resident subspecies of white-crowned sparrow (Zonotrichia leucophrys) - Jesse S. Krause; Trevor Watkins; Angus M. A. Reid; Jeffrey C. Cheah; Jonathan H. Pérez; Valerie R. Bishop; Marilyn Ramenofsky; John C. Wingfield; Simone L. Meddle (Oecologia, 2022)

Breeding on the leading edge of a northward range expansion: differences in morphology and the stress response in the arctic Gambel’s white-crowned sparrow - Jesse S. Krause; Helen E. Chmura; Jonathan H. Pérez; Lisa N. Quach; Ashley Asmus; Karen R. Word; Michaela A. McGuigan; Shannan K. Sweet; Simone L. Meddle; Laura Gough; Natalie Boelman; John C. Wingfield (Oecologia, 2016)

From neurons to nests: nest-building behaviour as a model in behavioural and comparative neuroscience - Zachary J. Hall; Simone L. Meddle; Susan D. Healy (Journal of Ornithology, 2015)

Influence of sex steroid hormones on spatial memory in a songbird - Zoë G. Hodgson; Simone L. Meddle; Julian K. Christians; Todd S. Sperry; Susan D. Healy (Journal of Comparative Physiology A, 2008)

Endocrine responsiveness to social challenges in northern and southern hemisphere populations of Zonotrichia - John C. Wingfield; Simone L. Meddle; Ignacio Moore; Shallin Busch; Douglas Wacker; Sharon Lynn; Aaron Clark; Rodrigo A. Vasquez; Elizabeth Addis (Journal of Ornithology, 2007)